PRONOSTIC FACTORS ASSOCIATED WITH BAD EVOLUTION IN PATIENT OPERATED HIP FRACTURE OVER 65 YEARS OLD - Vento Benel, Renee Flor (2019)
Introduction: Hip fracture in the elderly is the most common cause of hospitalization in the trauma department, causing repercussion in several clinical areas, affecting its independence. Objective: To determine the prognostic factors of poor evolution in the study population. Methods: Ambispective,correlational and non-experimental study was designed. The population consisted of all patients over 65 years of age who underwent surgery for hip fracture between January 2014 and July 2015 at the Central Hospital of the Pruvian Air Force (F.A.P). The magnitude of the association was quantified using the oddsratio, and a multivariate analysis was performed on the significant variables and a 6-month follow-up was performed. Results: The variables identified with a strong association with poor evolution were: age greater than 75 years (OR = 3,750 CI: 1,275-11,026 p = 0,016), high comorbidity (OR = 4.00 CI: 1.58 -10.08 p =0.003), hemoglobin <10 (OR 6,545 CI: 1.17-36.6 p = 0.0032), respiratory complication (OR 6.00 CI: 1.55-22.94 p = 0.000) patients in the 6-month follow-up. The previous fracture was strongly related to mortality (OR 3,665 CI: 1,366 - 9,821 p = 0,010). Conclusions: The poor evolution in hip fracture is associated with high comorbidity, age greater than 75 years, residence (institutionalized patient), postoperative respiratory complication with significant limitations in gait capacity and the functional status of the patients. Finally, the antecedent previous fracture showed high association with an increased mortality of patients at 6 months follow-up.